Biological Nanosensors On Network for Diabetes Control With Alert Emission for Users - Quijano Súarez , Edison Andres; Hurtado Acosta, Héctor Felipe; Castang Montiel, Gerardo Alberto (Ingeniería Solidaria, 2019)
Introduction: This paper is the product of the research "Biological network nanosensors for diabetes control with the issuance of alerts to users", developed in the technological faculty of the Francisco José de Caldas District University carried out during 2018 and 2019.Problem: Diabetes is a disease that affects most of the adult population and not having proper control can lead to health complications that lead to early deaths.Objective: To propose a theoretical prototype for communication between a nano network and the applications that work to monitor networks, which issues an alarm to users who have diabetes and thus have better control of their disease.Methodology: Research articles, books and forums published from 2010 onwards (some exceptions are found in the references) were used, along with official documentation of tools such as Netcool, Nagios and Pandora.Results: 66 sources were found including papers, monographs, forums and others that complied with the research guidelines. In addition, numerous applications were found that can be implemented in the proposed theoretical prototype.Conclusion: A theoretical prototype is proposed for communication between a nano network and an alarm management system for the end user. This prototype use current technologies and specialized tools.Originality: The article presents an innovative theoretical prototype, designed to solve a problem in the health sector, that makes use of emerging technologies. Limitations: The internet of nano-things, oriented to biological processes, is an emerging technology. At the time of writing this paper, there are no real prototypes or tools to simulate nano networks in conjunction with biotechnology.
Keywords: Nano-network; Nano-sensor; Nanotechnology; Nanoscience; Nano-medicine; Diabetes